Metrics for performance evaluation of safety applications in vehicular ad hoc networks - Yousefi, Saleh; Fathy, Mahmood (Transport, 2008)
In the recent years, direct message exchange between vehicles in order to improve the safety of road traffic has been attracting lots of interest in both networking and road safety communities. While travelling on a road, vehicles form an ad hoc network called Vehicular Ad hoc NETwork (VANET) and deploy life safety applications. Evaluating the performance of these applications is primordial for realizing VANETs in real life. Current literature lacks efficient ways to evaluate the performance of safety applications and mostly leverages on classical networking metrics like delay, delivery rate etc. In this paper, we consider both networking and safety concerns simultaneously to come up with more efficient methods. In particular, we first point out the significance of fairness and coverage from safety viewpoint. Then, we introduce two new metrics called beaconing rate and effective range aiming at providing more facilities for safety performance evaluation in VANET s research. Furthermore, realizing special characteristics of safety applications while disseminating beacon messages, we study the way that beacon dissemination protocols affect the performance of safety applications. We then conduct extensive simulation study to show the usefulness of the introduced metrics and derive some insights on the feasibility of driver‐assistant safety applications. Our evaluation also shows that sending the aggregated status of neighbouring vehicles in addition to vehicle's own status, and instead, increasing beacon transmission interval may be invoked in order to assist safety applications in providing satisfactory services to drivers.First published online: 27 Oct 2010